Sartre and Mauss - Sass, Simeão (2025)
The present study analyzes the relations between Mauss and Sartre. It investigates, primarily, the connections between the obligation of reciprocating a gift and the consequences of this symbolic act, to elaborate a morality deemed as a total fact. Freedom stands out, in this context, as a fundamental value.